Child welfare and rights differences in common law and civil law perspectives - O'Halloran, Kerry (Children and the law, 2024)
This book examines jurisdictional differences in the role of the principle of the welfare interests of the child in common and civil law, and focuses on differences within these two legal traditions. By identifying and analysing the functions of the principle both in the public and private sector of family law, the book compares and contrasts different jurisdictions, and assesses their capacity to implement children's welfare interests and rights. Covering a variety of topics including child abuse and neglect, state care, adoption and reproductive rights and family breakdown, the book demonstrates how welfare interests and rights can be balanced to create a coherent framework for family law. In addition to providing an up-to-date digest of cases and legislation, the book will be of interest to researchers in the field of child welfare and family law"--